Answer: 2 1/3
Explanation:
10 2/6 - 7 5/6
You can make both a fraction by multiplying the denominator by the whole number, and then adding the numerator to that number, and keeping the denominator the same. So, 10*6 = 60 and 60 + 2 = 62 and you keep the denominator as 6, which would make 62/6
7*6 = 42 and 42 + 5 = 47 so 7 5/6 becomes 47/6
10 2/6 is equivalent to 62/6
7 5/6 is equivalent to 47/6
This just makes it easier to look at.
Now you just work through the equation.
62/6 - 47/6 = 15/6
15/6 = 2 3/6 = 2 1/3
<span>LMNO is a parallelogram
so NM = OL
x + 15 = 3x + 5
solve for x
x - 3x = 5 - 15
-2x = -10
x = 5
Answer
x = 5</span>
Answer
multiplication
Step-by-step explanation:
Answer:
This sum is the sum of an arithmetic sequence. There is a formula for the sum of an arithmetic sequence which can be looked up or derived by a variety of means.
A nice approach for this sequence is the following. Notice that the sum of first and last number in the sequence is the same as the sum of the second and second last, and also the same as the sum of the third and third last, and so on.
There are n of these pairs. So the desired sum is n x (first number + last number). But the first number is 1 and the last on is 2n. Thus the desired sum is n(1 + 2n).
Hope this helps!!
Mark Brainleast!!!!!!!!!!!
Answer:
V(x) = (x +4)(x +2)(2x +11)
Step-by-step explanation:
For length L = (x+4), the height is ...
2L +3 = 2(x+4) +3
= 2x +8 +3
= 2x +11
The volume is the product of length, width, and height, so is ...
V = (x +4)(x +2)(2x +11)